1976
DOI: 10.1128/jb.125.2.616-625.1976
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of carotenoid-producing and albino strains of Neurospora crassa by visible light, blacklight, and ultraviolet radiation

Abstract: Suspensions of Neurospora crassa conidia were inactivated by blacklight (BL) radiation (300 to 425 nm) in the absence of' exogenous photosensitizing compounds. Carotenoid-containing wild-type conidia were less sensitive to BL radiation than albino conidia, showing a dose enhancement factor (DEF) of 1.2 for dose levels resulting in less than 10%. survival. The same strains were about equally sensitive to shortwave ultraviolet (UV) inactivation. The kinetics of BL inactivation are similar to those of photodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

1977
1977
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…Hematochrome accumulation is induced by UV-B, suggesting a UV-protective role (55). However, studies with Phycomyces blakesleeanus (56), Neurospora crassa (57) and Halobacterium spp. (58) showed no significant screening by carotenoids.…”
Section: Uv Optics Of C Nivalis Cellsmentioning
confidence: 99%
“…Hematochrome accumulation is induced by UV-B, suggesting a UV-protective role (55). However, studies with Phycomyces blakesleeanus (56), Neurospora crassa (57) and Halobacterium spp. (58) showed no significant screening by carotenoids.…”
Section: Uv Optics Of C Nivalis Cellsmentioning
confidence: 99%
“…Although no detailed analysis has been made to analyze the chemical composition of these pigments, their yellow and orange colors resemble carotenoids (2). Carotenoids were found to protect microorganisms from near UV and visible light damage by quenching triplet-state photosensitizers and reactive oxygen species (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Photosensitized inactivation, the dye-mediated killing of organisms by light, was first reported by Raab in 1900 (15). Since that time, it has been shown that a wide variety of microorganisms, including viruses (8,21), bacteria (9,10), and fungi (2,4), can be killed in vitro by photosensitization. Recently this technique has been applied in vivo for the treatment of herpes simplex virus infections.…”
mentioning
confidence: 99%